ESTIMATION YIELD AND YIELD COMPONENTS OF PROMISING CHICKPEA GENOTYPES UNDER DIFFERENT LEVELS OF CHALLENGE HERBICIDE - HUSSAIN, MOHAMMED ALI; RASHID, ABDULMALIK MOHAMED; NAIF, REBAR SULEIMAN; SULEIMAN, VIAN YOUNIS (Journal of Duhok University, 2023)
A field experiment was carried out in sandy clay loam during winter season 2020-2021 at the field of Agricultural Research Center, Duhok. Two promising chickpea genotypes (FLipo7-223C and FLipo7-245C) using in this study derived from crosses per formed at international center for Agricultural research in Dry Areas (ICARDA). Four levels of challenge herbicide use 0, 0.5, 1.5 L ha-1). The experimental units were laid out in randomize complete block design in three replicates. The results indicated that the Flip 07-245 c chickpea genotype was superior in first pod height (29.5 cm), main and secondary branch per plant (4.383 and 6.808), 100 seed weight (40.409),number of nodules per plant (84.83) ,number of pods per plant (42.67) and total seed yield (267.89),while the best challenge herbicide was 1.5 l ha-1 because the dose gave the lowest value 8.5, broad leafed weed and 2.33 for narrow leafed weed, there for the seed yield increase with the increase the rate of challenge herbicide. The seed yield correlated positive and significantly with first pod height (0.35), number of nodules per plant 0.828, number of pods per plant (0.537), number of main branchy (0.774) and secondary branches per plant (0.683), while negative significantly with number of broad leaved weed (-0.675) and plant height (-0.705)